Censorship detected in NI (Nicaragua) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Nicaragua. Data sourced from CensoredPlanet.
Censorship Incident ID: NI-2026-0001. Severity: critical. Confidence: 65%